Carcass characteristics of zebu steers receiving different oleaginous grains - doi: 10.4025/actascianimsci.v35i3.14533 - Oliveira, Dalton Mendes; Ladeira, Márcio Machado; Bassi, Marcelo Silva; Chizzotti, Mário Luiz; Machado Neto, Otávio Rodrigues; Busato, Karina Costa (Acta Scientiarum. Animal Sciences, 2013)
This research aimed to evaluate carcass traits of Zebu steers fed different oleaginous grains. Thirty one 23 months old zebu steers with 365 + 37.5 kg of live weight were used. The diets consisted ofcorn silage and four different concentrates; no additional lipids and three different ground oilseeds sources: soybean, cottonseed and linseed. The diets had concentrate:roughage ratio of 60:40 and were offered ad libitum. The experimental period was of 84 days, preceded by a 28 day adaptation period. The experiment was carried out in a randomized block design and the means were compared by Scott-Knott test at 5% level of probability. The CS inclusion of into the diet decreased (p < 0.05) carcass yield of the animals. The hindquarter was heavier (p < 0.05) with the addition of SB to the diet. The spare ribs had the highest performance (p < 0.05) and outside flat was heavier (p < 0.05) when the animals were submitted to CS and FS diets. The CS addition to the diet improved carcass characteristics.